Business Format Franchising - The next market entry model for Boots Retail International? - Powell, Andrew (2005)
This dissertation is based in the field of international retailing and in particular, the value and challenges associated with employing franchising as a vehicle for international retail expansion. Its focus is on The Boots Group (TBG) and specifically its loss-making subsidiary BRI (Boots Retail International).Despite its loss- making label, BRI is currently enjoying a significant upturn in fortune,on the back of very positive profitable growth figures, which have generated an increased enthusiasm for expanding the number of markets BRI is currently actively trading in. This has lead to the challenge of investigating whether BRI should develop a retail business format franchise for application as a relatively risk free method of market entry and if so what market offers the best option for testing this franchise system.